The intuitionistic fuzzy analytic hierarchy model for nicotine replacement therapy decision making problem / Norfazillah Matmali, Nowyannie Willie D. Tamsin and Zamali Tarmudi - Matmali, Norfazillah; Tamsin, Nowyannie Willie D.; Tarmudi, Zamali (Universiti Teknologi MARA, Sabah, 2022)
Despite the fact that smoking is the main cause of tobacco-related death, the smoking population continues to rise. To address this problem, Nicotine Replacement Therapy (NRT) was established as a smoking cessation method to reduce the number of smokers. NRT decision-making process requires a large amount of data. However, very little attention has been paid to NRT decision-making using multi-criteria decision-making (MCDM) to assist health decision-makers. To address this issue, a systematic MCDM procedure was utilised to examine the decision-making dilemma in NRT. Both quantitative and qualitative data were used to provide more comprehensive findings. The current work utilised the Intuitionistic Fuzzy Analytic Hierarchy Procedure (IF-AHP) approach to provide a more systematic, comprehensive, and adaptable decision-making process. To capture fuzziness, ambiguity in decision-making, and vagueness of information caused by human language and issue subjectivity, the intuitionistic fuzzy set (IFS) was employed. The present case study illustrated the suggested model's practicality in coping with uncertainty in NRT decision making process. The suggested model fit the local environment and was validated using the NRT decision-making issue. Findings from this study also suggest that the IF-AHP approach is an appropriate decision tool in NRT decision-making process.